I know that (big book) - Loves, June (Nelson Australia Melbourne, 1994)
"I Know That" by Junes Love is a thoughtful children's book that explores themes of knowledge, curiosity, and self-discovery. Through simple yet engaging text, the story encourages young readers to reflect on what they know about themselves and the world around them. The narrative often invites children to think critically and embrace their unique perspectives, fostering a sense of confidence and individuality. With charming illustrations, the book makes learning fun and interactive, making it a delightful read for early learners and a great addition to storytime.